Alpha-defensins determination in different types of synovial fluid and parallel collected serum samples by ELISA - Pavlina Kusnierova (Palacký University Olomouc, Faculty of Medicine and Dentistry, 2021)
Aims. The study aims were to verify the serum (S) and synovial fluid (SF) reference intervals (RIs) for human neutrophil defensins (HNP1-3); measure S and SF defensin concentrations in different types of SF, including non-inflammatory, inflammatory non-pyogenic, inflammatory pyogenic, and hemorrhagic; and to compare the HNP1-3 concentrations in SF and S with those of other inflammatory biomarkers. Methods. SF and S samples were collected from 92 patients. HNP1-3 concentrations were determined using enzyme-linked immunosorbent assays; glucose, lactate, interleukin-6, and procalcitonin using an automatic analyzer; and presepsin using a Pathfast system. There were 61 non-inflammatory, 11 inflammatory non-pyogenic, 11 inflammatory pyogenic, and 9 hemorrhagic SF. Non-inflammatory SF was divided into non-inflammatory normal and non-inflammatory osteoarthritis. The former was used to estimate the HNP1-3 RI in SF and S. Results. The estimated HNP1-3 RIs of SF and S were 12.47-437.42 mg/L and 5.45-44.75 µg/L, respectively. HNP1-3 differed significantly between S and SF and individual groups of SF (P<0.001 and P=0.001, respectively). There were significant relationships between SF HNP1-3 and S HNP1-3 (P<0.001), S C-reactive protein (P<0.001), and S interleukin-6 (P=0.007), and between SF HNP1-3 and SF C-reactive protein (P=0.004) and SF interleukin-6 (P<0.001). The highest kappa coefficient was between SF HNP1-3 and SF interleukin-6 (κ=0.507). Conclusions. We validated the SF HNP1-3 diagnostic kit and demonstrated that SF and S HNP1-3 are promising biomarkers for distinguishing inflammatory from non-inflammatory joint diseases.